2010
DOI: 10.1038/jp.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Fetal middle cerebral artery Doppler fluctuations after laser surgery for twin–twin transfusion syndrome

Abstract: Objective: The objective of this study was to compare alterations in the middle cerebral artery (MCA) pulsatility index (PI) and mean velocity (V mean ) after laser surgery for twin-twin transfusion syndrome (TTTS).Study Design: MCA Doppler studies were conducted 1 day before and after laser surgery for TTTS. The pre-and postoperative mean (standard deviation) of the MCA PI and V mean z-scores of the recipient and donor fetuses were calculated and compared. Data were analyzed using paired testing and multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…34 The etiology of the lower MCA PI and abnormally low CPR in our population of RTs who went on to develop cardiomyopathy is unclear and may have to do with placental abnormalities versus an effect from cardiac output. Previous studies have shown a similar finding of lower MCA PI in untreated RTs, 35,36 though these studies included twins with more advanced disease and overt cardiac findings. Although DTs often have growth restriction, RTs generally have growth in the normal range for gestational age.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…34 The etiology of the lower MCA PI and abnormally low CPR in our population of RTs who went on to develop cardiomyopathy is unclear and may have to do with placental abnormalities versus an effect from cardiac output. Previous studies have shown a similar finding of lower MCA PI in untreated RTs, 35,36 though these studies included twins with more advanced disease and overt cardiac findings. Although DTs often have growth restriction, RTs generally have growth in the normal range for gestational age.…”
Section: Discussionsupporting
confidence: 63%
“…A study by Williams et al 48 found cerebroplacental Doppler abnormalities before 23 weeks' gestation to be predictive of impaired postnatal neurodevelopment in fetuses with congenital heart disease. Aghajanian et al 36 evaluated MCA PI in fetuses with TTT, and found that RTs had lower MCA PI Z scores compared with DTs, which was found to increase significantly after laser therapy. These findings would indicate that laser therapy was effective at treating the underlying cause of RT brain sparing.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, most donors showed a reduction in UAPI, MCAPI and MCAPSV, while the majority of the recipients showed increased resistance in UA blood flow (UAPI) and an increase in MCAPI and MCAPSV after the procedure. Our results are similar to those of various papers (20)(21)(22) in which fetal vasoconstriction maintained blood pressure and minimised changes in cerebral blood flow secondary to the drop in systemic blood flow in recipients after FLP, leading to an increase in MCAPI.…”
Section: Ttts the Eurofetus Study Demonstrated That Pregnancies Compsupporting
confidence: 91%
“…The fetal hemodynamic changes in TTTS pregnancies undergoing laser surgery has been the subject of debate in a few studies. 8,[25][26][27][28] In only one small cohort, studying 99 children, a correlation was found between an abnormal postlaser CPR and long-term developmental outcomes. 8 Data from our study further increase the awareness regarding the potential relationship between fetal perioperative hemodynamic changes and NDI.…”
Section: Discussionmentioning
confidence: 96%